Karakter Pendidik Perspektif Al-Qur’an Surah Quraisy Ayat 1-4 - Izzan, Ahmad; Rahmawati, Risma (STAI Al-Musaddadiyah Garut, 2024)
The character of an educator not only determines his authority in front of students, but also in front of society. The personality characteristics of a good educator are very important for educators so that they can control and control the behavior of their students through habituation patterns. It would be a big mistake if an educator only taught students memorization and memory material without paying attention to aspects of their attitudes and social skills. Habituating good attitudes and providing social skills is very important to build students' character. The aims of this research are; 1) Describe the character of the educator; 2) Describe the character of educators from the perspective of Al-Qur'an Surah Quraisy verses 1-4. The method used in this research is qualitative methods, while data collection techniques are used with documentation, which comes from primary data from the Qur'an and hadith and secondary tafsir-tafsir as well as other sources relevant to this research, analysis techniques The data used is Maudhu'i's interpretation. From the research results, it was found that the Al-Qur'an Surah Quraish verses 1-4 do not directly talk about the character of educators, but there are indicators of the character of educators in the Al-Qur'an Surah Quraish verses 1-4, namely creative, broad-minded and faithful. Keywords: Educator Character, Creative, Broad Thinking, Faith and Al-Qur'an Surah Quraish Verses 1-4.